Effects of annealing on optical and structural properties of zinc oxide nanocrystals. Issue 11 (25th August 2015) - Khachadorian, Sevak; Gillen, Roland; Choi, Sumin; Ton‐That, Cuong; Kliem, André; Maultzsch, Janina; Phillips, Matthew R.; Hoffmann, Axel
Abstract: The optical and vibrational properties of zinc oxide nanocrystals (ZnO NCs), grown by chemical precipitation method, were investigated following thermal annealing treatments in oxygen, argon, and zinc vapors at temperatures up to 900 ∘ C. Raman scattering and photoluminescence techniques were utilized to show the effect of temperature annealing in various environments on optical and structural properties of ZnO NCs, referring them to the reduction and increase of certain intrinsic defect concentrations. The experimental results are complemented by density functional theory calculations for understanding the correlation between Raman modes induced with different annealing procedures and certain intrinsic point defects.